2019
DOI: 10.1155/2019/4578175
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase Hyperactivity Contributes to Cardiac Dysfunction and Apoptosis in Rats with Severe Experimental Pancreatitis through ROS-Mediated MAPK Signaling Pathway

Abstract: NADPH oxidase (Nox) is considered a major source of reactive oxygen species (ROS) in the heart in normal and pathological conditions. However, the role of Nox in severe acute pancreatitis- (SAP-) associated cardiac injury remains unclear. Therefore, we aim to investigate the contribution of Nox to SAP-associated cardiac injury and to explore the underlying molecular mechanisms. Apocynin, a Nox inhibitor, was given at 20 mg/kg for 30 min before SAP induction by a retrograde pancreatic duct injection of 5% sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…NADPH oxidase activity is increased in heart failure 22 . Apocynin is known to inhibit NADPH oxidase and oxidative stress 10,23 . In the present study, we found that apocynin improved LV function after MI.…”
Section: Discussionsupporting
confidence: 63%
“…NADPH oxidase activity is increased in heart failure 22 . Apocynin is known to inhibit NADPH oxidase and oxidative stress 10,23 . In the present study, we found that apocynin improved LV function after MI.…”
Section: Discussionsupporting
confidence: 63%
“…Canonical MAPK signaling is mediated through three-kinase cascades beginning with an upstream MAPKKK (MEKK) and leading sequentially to MEK and to effector MAPKs, such as c-Jun N-terminal kinases (JNK), p38 and extracellular signal-regulated kinases (ERK) [ 22 ]. It is important to highligh that JNK, p38 and ERK are considered redox-sensitive kinases, and their activity is usually reported to regulate inflammation and apoptosis of cardiomyocytes [ 60 , 61 ].…”
Section: Protein Kinase Activity In Rvh Under Hypobaric Hypoxia Exmentioning
confidence: 99%
“…Excessive ROS generation through NOX‐2 and NOX‐4 has been associated with apoptotic cell death of cardiac cells resulting in cardiac dysfunction and pathogenesis. It has been found that hyperactivation of NOX elevates ROS generation that further activates the MAPK pathway and promotes apoptosis in the myocardium that may cause cardiac injury in severe acute pancreatitis (SAP) 41 . Moreover, the deregulation of NOX‐2 contributes to angiotensin II‐induced cardiomyocyte hypertrophy, atrial fibrillation, and the development of interstitial fibrosis.…”
Section: Human Pathologies and Nox Connectionsmentioning
confidence: 99%